A Goths era church at the Voltorre priory in the Lake of Varese area. The archeological excavation of 2001. Data and assumptions (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2025)
The findings of the archeological excavation of 2001 demonstrated that the Voltorre Monastery was built over two pre-existing churches which, as at today, are still unknown. Out of the two, the better preserved one, presents a Byzantine church floor plan dating back to Gothic Era. The contextualization of the Church in the Comum-Verbanus orographic narrow shines new lights on the toponym “Voltorre”. Just outside the current Romanic church, a monumental necropolis had been developing in three different phases. The most notable building, which is attributable to a clergyman, is beside the area where it is supposed to lay the sacramental pool, which was buried at the center of the presbytery of the now-demolished Goth Era church and whose whereabouts could have been still known at that time, or perhaps, was rediscovered in that circumstance.
Keywords: Voltorre Monastery; Lake of Varese; Byzantine floor plan church; Goth age; orographic narrow, Comum-Verbanus Roman road, toponym, Medieval necropolis